FACTORS ASSOCIATED TO THE DEVELOPMENT OF THE ARTERIAL HYPERTENSION IN ADULT PEOPLE OF ANÁPOLIS (Fiep Bulletin - online, 2014)
The arterial hypertension is now one of the largest risk factors for the health in Brazil. The General objective of this study was to correlate factors associated to the development of the Arterial Hypertension in adult individuals of Anápolis. They were appraised through a questionnaire with 10 items, 203 (two hundred three) people with hypertension of both sexes with age between 13 and 90 years, residents in this city. To participate of the study the appraised he/she had to be a person with hypertension, to sign the term of illustrious free consent and to answer all the items of the questionnaire, being these: name; date of birth; sex; weight; height; blood pressure; education; color of the skin; how many times a week he/she practiced some physical activity; how long the session of physical activity lasted; if your activity was guided by somebody; which the types of physical activity that more practiced; in childhood, how many times a week he/she practiced some physical activity; it drinks coffee during the day; which the cause of your hypertension; it drinks water during the day; to yours to see, which the limitations of the person with hypertension. After the collection, the data were tabulated in a spreadsheet of SPSS version 10.0, where we applied the correlation test. The level of applied was of p
Keywords: Factors; Hypertension; Physical activity